Heterogeneous Hydroamination over Supported Ionic Liquid‐ Stabilized Copper Ions and Its Mechanistic Study. Issue 32 (13th November 2017) - Sengupta, Manideepa; Das, Subhasis; Bag, Arijit; Lefebvre, Frederic; Bordoloi, Ankur
Abstract: Cu II ions immobilized on supported ionic liquid phase (Cu@SILP), using imidazolium‐based ionic liquids grafted on functionalized multiwalled carbon nanotubes and efficiently utilised as catalyst in selective heterogeneous hydroamination of aromatic terminal alkynes with anilines. Large turnover numbers (TON) and selectivity (> 99%) towards Markovnikov's addition product was achieved. To recognize the structure‐activity relationship, the catalyst was characterized using Transmission electron microscopy (TEM), X‐ray photoelectron spectroscopy (XPS), Fourier transform infra‐red (FT‐IR) spectroscopy, solid state NMR. Further mechanistic pathway of hydroamination with Cu@SILP has been predicted by performing Density Functional Theory (DFT). Abstract : Effective grafting of Copper (II) ions immobilized ionic liquid over functionalized carbon nanotubes (Cu@SILP) and its application on catalysis for the synthesis of substituted aromatic amines via hydroamination. Further, probable mechanistic pathway has been predicted with DFT‐based calculations.